Fatores determinantes que influenciam o consumidor brasileiro a usar fintechs. - Fernandes, Kaue Augusto (2021)
The number of fintechs has grown each year in Brazil, competing with financial institutions, increasing the offer of financial products and services to consumers. However, there are still few studies that address the reasons why Brazilian consumers have used financial startups. The aim of this study is to understand the determining factors that have influenced consumers to use fintechs in Brazil. Based on this premise, the constructs of the UTAUT3 model were used, incorporating variables used in studies carried out in Germany, China and South Korea and validated in interviews with entrepreneurs in the fintech sector, namely: Brand Image, Trust, Data Security and Government. During the interview phase, it was suggested to assess whether Brand Identity has influenced consumers to use fintechs. A questionnaire was developed and disseminated to users through ads on Google and Facebook for those searching for the term fintech. 506 valid responses were obtained. Data were analyzed with the partial least squares structural equation model (PLS-SEM) to test the hypotheses. The results showed, of the twelve variables of the UTAUT3 model, six of them were supported. Among the studies carried out abroad, only the Brand Image and Data Security variables were supported. The Brand Identity variable did not have significant effects that influenced the intention to use fintechs. Thus, this study contributes to the literature on the factors that influence Brazilian consumers to use fintechs, providing a more comprehensive and current view of the interests of users and also with the market that will be able to understand how to win and/or keep customers.